2017
DOI: 10.1016/j.immuni.2017.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Sensing of Bacterial Cyclic Dinucleotides by the Oxidoreductase RECON Promotes NF-κB Activation and Shapes a Proinflammatory Antibacterial State

Abstract: SUMMARY Bacterial and host cyclic dinucleotides (cdNs) mediate cytosolic immune responses through the STING signaling pathway, though evidence suggests alternative pathways exist. We used cdN-conjugated beads to biochemically isolate host receptors for bacterial cdNs, and identified the oxidoreductase RECON. High-affinity cdN binding inhibited RECON enzyme activity by simultaneously blocking the substrate and co-substrate sites, as revealed by structural analyses. During bacterial infection of macrophages, REC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
112
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(113 citation statements)
references
References 54 publications
1
112
0
Order By: Relevance
“…In mammals, cGAMP and linear oligoadenylate are important innate-immune signals, synthesized by cGAS (cyclic GMP-AMP synthase) and OAS (oligoadenylate synthase) family proteins in response to cytoplasmic DNA or double-stranded RNA (Chen et al, 2016;Hornung et al, 2014). Nucleotide-based second messengers also mediate cross-kingdom signaling, with mammalian innate immune receptors able to recognize and respond to a variety of bacterially-generated second messengers (Burdette et al, 2011;McFarland et al, 2017;.…”
Section: Introductionmentioning
confidence: 99%
“…In mammals, cGAMP and linear oligoadenylate are important innate-immune signals, synthesized by cGAS (cyclic GMP-AMP synthase) and OAS (oligoadenylate synthase) family proteins in response to cytoplasmic DNA or double-stranded RNA (Chen et al, 2016;Hornung et al, 2014). Nucleotide-based second messengers also mediate cross-kingdom signaling, with mammalian innate immune receptors able to recognize and respond to a variety of bacterially-generated second messengers (Burdette et al, 2011;McFarland et al, 2017;.…”
Section: Introductionmentioning
confidence: 99%
“…The present study revealed that sanqixiantao extracts alleviated the inflammation and significantly decreased the serum levels of pro-inflammatory cytokines such as TNF-α and IL-6 [24]. Bacterial infections usually result in the exacerbation of wounds and severe inflammatory reactions [25]. The results also demonstrated that sanqixiantao extract had significant antibacterial activities against six pathogenic bacteria that cause wound infection (E. coli, S. aureus, P. aeruginosa, S. epidermidis, C. perfringens and C. tetani).…”
Section: Discussionmentioning
confidence: 51%
“…The ER membrane adaptor ERAdP was recently identified as a direct sensor for c‐di‐AMP . Mouse oxidoreductase RECON has been classified as a sensor for some bacterial CDNs which modulate NF‐κB activation independently of STING through which they shape a proinflammatory antibacterial response . Here, we determined that the DNA sensor cGAS is involved in the engagement of endocytosed eCDNs, prior to STING activation.…”
Section: Discussionmentioning
confidence: 93%